ChemInform Abstract: Stable Room Temperature Magnetic Ordering and Excellent Catalytic Activity of Mechanically Activated High Surface Area Nanosized Ni0.45Zn0.55Fe2O4. Issue 49 (December 2015) - Dey, S.; Gomes, R.; Mondal, R.; Dey, S. K.; Dasgupta, P.; Poddar, A.; Reddy, V. R.; Bhaumik, A.; Kumar, S.
Abstract: Nanosized Ni0.45 Zn0.55 Fe2 O4 (≈12 nm) is prepared by high‐energy ball milling of powders of extremely pure Ni0.45 Zn0.55 Fe2 O4 (330 rpm, 50 h) which itself is obtained by sintering and annealing of the metal oxides (950 °C, 12 h and 700 °C, 12 h).